Women in the inquisition: Spain and the new world - Giles, Mary E. (Johns Hopkins University Press, 1999)
Mari S(c)Łnchez and In(c)♭s Gonz(c)Łlez: conflict and cooperation among crypto-Jews / Gretchen Starr-Lebeau -- In(c)♭s of Herrera del Duque: the prophetess of extremadura / Haim Beinart -- Mar(c)Ưa L(c)đpez: a convicted judaizer from Castile / Ren(c)♭e Levine Melammed -- Francisca Hern(c)Łndez and the sexuality of religious dissent / Mary E. Giles -- Mar(c)Ưa de Cazalla: the grievous price of victory / Angel Alcal(c)Ł -- Francisca de los ap(c)đstoles: a visionary voice for reform in sixteenth-century Toledo / Gillian T.W. Ahlgren -- Y yo dije, "S(c)Ư senor": Ana Domenge and the Barcelona inquisition / Elizabeth Rhodes -- Mar(c)Ưa de Jes(c)ðs de Agreda: the sweetheart of the holy office / Clark Colahan -- Contested identities: the Morisca visionary, Beatriz de Robles / Mary Elizabeth Perry -- When bigamy is the charge: Gallegan women and the holy office / Allyson M. Poska -- "More sins than the Queen of England": Marina de San Miguel before the Mexican inquisition / Jacqueline Holler -- Blasphemy as resistance: an African slave woman before the Mexican inquisition / Kathryn Joy McKnight -- Rosa de Escalante's private party: popular female religiosity in colonial Mexico City / Linda A. Curcio-Nagy -- Testimony for canonization or proof of blasphemy?: the new Spanish inquisition and the hagiographic biography of Catarina de San Juan / Kathleen Myers